2013
DOI: 10.1002/ece3.717
|View full text |Cite
|
Sign up to set email alerts
|

Forest insects and climate change: long‐term trends in herbivore damage

Abstract: Long-term data sets, covering several decades, could help to reveal the effects of observed climate change on herbivore damage to plants. However, sufficiently long time series in ecology are scarce. The research presented here analyzes a long-term data set collected by the Hungarian Forest Research Institute over the period 1961–2009. The number of hectares with visible defoliation was estimated and documented for several forest insect pest species. This resulted in a unique time series that provides us with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 48 publications
(96 reference statements)
2
61
1
4
Order By: Relevance
“…The infl uence of average temperature in the different time windows recorded in this study differs from that previously reported (Wagenhoff & Veit, 2011;Klapwijk et al, 2013). The highest explanatory power was recorded for the May to July period.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The infl uence of average temperature in the different time windows recorded in this study differs from that previously reported (Wagenhoff & Veit, 2011;Klapwijk et al, 2013). The highest explanatory power was recorded for the May to July period.…”
Section: Discussioncontrasting
confidence: 99%
“…Climate change therefore may for example cause range expansion (Vanhanen et al, 2007;Battisti, 2008;Jepsen et al, 2008;Battisti & Larsson, 2015;Battisti et al, 2017), either decrease or increase the number of generations in multivoltine species (Ayres & Lombardero, 2000;Jöns-son et al, 2009) and alter their interactions with their host plants (Pelini et al, 2009;Robinet & Roques, 2010) and natural enemies (Jeffs & Lewis, 2013;Kalinkat & Rall, 2015). The summation of these different effects can have a signifi cant effect on population fl uctuations, outbreaks and damage by forest insects (Mattson & Haack, 1987;Leskó et al, 1995Leskó et al, , 1998Csóka, 1997;Rouault et al, 2006;Dobbertin et al, 2007;Jactel et al, 2012;Klapwijk et al, 2013;Hlásny et al, 2015). the population fl uctuations, as already suggested in several earlier papers (Klapwijk et al, 2013;Wagenhoff & Veit, 2011;Wagenhoff et al, 2013Wagenhoff et al, , 2014.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Long-term surveys and examination of outbreak dynamics of five species of European Lepidoptera between 1800 and 2011 revealed climate-driven changes in outbreak severity, cyclicity, and frequency, but there were mixed effects of temperature on outbreak activity [12,26,27]. It is often argued that the frequency and severity of C. fumiferana outbreaks in North America have increased in the twentieth century.…”
Section: Introductionmentioning
confidence: 99%